Money demand in Europe: Evidence from the past - Christian Müller; Elke Hahn (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
The conditions under which European monetary policy is likely to be conducted are investigated by means of multi-variate time series modelling using aggregated data of all eleven European Monetary Union member states. A cointegration analysis identifies two stable long-run relationships within a set of five key macroeconomic variables, one of which can be interpreted as a money demand function and a sec(md one as a long term real interest rate (Fisher parity). Our findings indicate that monetary authorities might well be able to base their policy on the existence of a money demand. Particular emphasis is given both to the data sources and their aggregation, by providing a transparent account of our calculation procedure, which is not yet common in the existing literature.
urn:nbn:de:kobv:11-10047427
Keywords: E41; E52; C32; 330; european money demand; monetary targeting; aggregation